Spatial-temporal variation and tradeoffs/synergies analysis on multiple ecosystem services: A case study in the Three-River Headwaters region of China. (September 2020) - Zheng, Defeng; Wang, Yanhui; Hao, Shuai; Xu, Wenjing; Lv, Leting; Yu, Shuai
Highlights: Distribution of ecosystem services in the Three-River Headwaters region is obviously different. Regulating services are the largest in all ecosystem services. Synergies are the dominant correlation of ecosystem services in the Three-River Headwaters region. The strength of a same pair-wise ecosystem services varies at different scales. Abstract: We analyzed the spatial-temporal variation of ecosystem services in the Three-River Headwaters (TRH) region from 1990 to 2015 and their tradeoffs/synergies at the county-scale and grid-scale by using ecosystem service value model, correlation coefficient and bivariate spatial autocorrelation analysis. The results showed that: (i) From 1990 to 2015, the ecosystem services value (ESV) of the TRH region showed an upward trend, an increase of 60.681 billion yuan from 126.967 billion yuan in 1990 to 187.648 billion yuan in 2015. Moreover, the dynamic degree of ecosystem services was 6.59%. Regulating services accounting for 69.51% were the largest in all ecosystem services, followed by supporting, provisioning, and cultural services. Among the individual ecological services, only the values of gas regulation and environment depuration decreased, other services increased. Among various land use, the ecosystem services of grassland accounting for 47% were the largest, followed by watershed, wetland, forestland, desert, and farmlands. (ii) The spatial distribution of ecosystem services showed an increasing pattern from northwest to southeast. High-value areas of ecosystem services per unit area distributed in the lakes and basins of Zhidoi county, Madoi county, and Tanggulashan town. Low-value areas mainly distributed in the northwest of Zhidoi county. (iii) There was a significant positive correlation between climate regulation and soil conservation. Aesthetic landscape and all provisioning services were weak synergies, gas regulation and other services were weak tradeoffs. (iv) Analysis of multi-scale tradeoffs/synergies showed that synergies dominated ecosystem services, and tradeoffs transformed into synergies with the increase of scale. Quantifying the ESVs and clarifying the correlations among multiple ecosystem services at multi-scale can provide a basis for regional planning, and promote the sharing of ecological well-being among the people in the TRH region.